Human Papillomavirus Type 16 Sequence Variation in Concurrent Vulvar and Penile Carcinoma in a Married Couple. Issue 6 (June 2015) - Mitamura, Takashi; Watari, Hidemichi; Yamashiro, Katsushige; Kato, Tatsuya; Hosaka, Masayoshi; Shimada, Chisa; Fukumoto, Shun; Noshiro, Kiwamu; Sasaki, Takayuki; Sakuragi, Noriaki
Abstract : Abstract: We encountered an elderly married couple with concurrent vulvar and penile carcinoma with an Asian variant of human papillomavirus type 16. Asian variants might have an elevated risk of concurrent external genital carcinomas of a male and a female, and analysis of human papillomavirus variants might be important to understand the mechanism of carcinogenesis. Abstract : Occurrence of simultaneous genital malignancies associated with an Asian variant of human papillomavirus type 16 in a married couple supports the increased carcinogenicity of Asian subtypes.